Atmospheric Characterization of the Super-Jupiter HIP 99770 b with KPIC - Yapeng Zhang; Jerry W. Xuan; Dimitri Mawet; Jason J. Wang; Chih-Chun Hsu; Jean-Bapiste Ruffio; Heather A. Knutson; Julie Inglis; Geoffrey A. Blake; Yayaati Chachan; Katelyn Horstman; Ashley Baker; et al. (The Astronomical Journal, 2024)
Young, self-luminous super-Jovian companions discovered by direct imaging provide a challenging test for planet formation and evolution theories. By spectroscopically characterizing the atmospheric compositions of these super-Jupiters, we can constrain their formation histories. Here we present studies of the recently discovered HIP 99770 b, a 16 M _Jup high-contrast companion on a 17 au orbit, using the fiber-fed high-resolution spectrograph KPIC ( ${ \mathcal R }$ ∼ 35,000) on the Keck II telescope. Our K -band observations led to detections of H _2 O and CO in the atmosphere of HIP 99770 b. We carried out free retrieval analyses using petitRADTRANS to measure its chemical abundances, including the metallicity and C/O ratio, projected rotation velocity ( $v\sin i$ ), and radial velocity (RV). We found that the companion’s atmosphere has C/O $=\,{0.55}_{-0.04}^{+0.06}$ and [M/H] $=\,{0.26}_{-0.23}^{+0.24}$ (1 σ confidence intervals), values consistent with those of the Sun and with a companion formation via gravitational instability or core accretion. The projected rotation velocity $v\sin (i)\lt 7.8$ km s ^−1 is small relative to other directly imaged companions with similar masses and ages. This may imply a nearly pole-on orientation or effective magnetic braking by a circumplanetary disk. In addition, we added the companion-to-primary relative RV measurement to the orbital fitting and obtained updated constraints on orbital parameters. Detailed characterization of super-Jovian companions within 20 au like HIP 99770 b is critical for understanding the formation histories of this population.